Feasibility of magnetic resonance imaging‐ultrasound guided high‐dose‐rate brachytherapy for localized prostate cancer: Preliminary results from a prospective study - Kamitani, Nobuhiko; Miyaji, Yoshiyuki; Tamada, Tsutomu; Yoden, Eisaku; Kawata, Yujiro; Watanabe, Kenta; Tokiya, Ryouji; Nagai, Atsushi; Katsui, Kuniaki (International Journal of Urology, 2022)
Objective This study aimed to investigate preliminary outcomes of a prospective trial of magnetic resonance imaging‐ultrasound fusion‐guided ultrafocal high‐dose‐rate brachytherapy in localized prostate cancer. Methods In our prospective study, data from patients who underwent this treatment between April 1, 2020 and March 31, 2021 were analyzed. In the procedure, the applicator needle was inserted through the perineum to target the lesion on the multiparametric magnetic resonance imaging, which was fused onto the transrectal ultrasound image. The prescription dose was set at a single fraction of 19 Gy. Data from patients who received whole‐gland high‐dose‐rate brachytherapy were extracted and compared with data from patients who received ultrafocal high‐dose‐rate brachytherapy, to evaluate the frequency of acute adverse events. Results Eight patients underwent ultrafocal high‐dose‐rate brachytherapy with a median observation period of 7.75 months (range 5.96–15.36 months). No acute genitourinary or gastrointestinal adverse events were observed in this cohort. The planned procedure was completed in all patients, and no unexpected adverse events were observed; however, prostate‐specific antigen failure was detected in one patient. In the 25 patients who underwent whole‐gland high‐dose‐rate brachytherapy, acute genitourinary and gastrointestinal adverse events were observed in 88% and 20% of the patients, respectively. Ultrafocal high‐dose‐rate brachytherapy was a significant factor in avoiding acute adverse genitourinary events in univariate and multivariate analyses (P < 0.001 and P = 0.032, respectively). Conclusions Magnetic resonance imaging‐ultrasound fusion‐guided ultrafocal high‐dose‐rate brachytherapy in localized prostate cancer is a safe and feasible treatment without acute genitourinary and gastrointestinal adverse events. Long‐term observation and further investigation are warranted.